2015
DOI: 10.1103/physrevb.92.035128
|View full text |Cite
|
Sign up to set email alerts
|

Direct and third-body mediated resonance energy transfer in dimensionally constrained nanostructures

Abstract: The process of resonance energy transfer (RET) in a nanostructure influenced by a vicinal, nonabsorbing third body is studied within the framework of molecular quantum electrodynamics. Direct RET and the influence of neighboring matter have been studied previously, mainly for molecules. However, a complete study or unified understanding of direct and indirect RET in nanostructures with different dimensionalities is still lacking. Therefore, there is a strong need for a complete theory that models RET for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 40 publications
0
35
1
Order By: Relevance
“…k the reduced Plank's constant, ρ is the density of final states of the acceptor, M (2) ,M (4) are second and fourth order coupling matrix elements respectively. Furthermore, the third term represents the quantum interference of the RET process and signifies the controllability of the RET due to the laser field.…”
Section: (A) (D) the Results Demonstrate That Even For Moderate Lasmentioning
confidence: 99%
See 1 more Smart Citation
“…k the reduced Plank's constant, ρ is the density of final states of the acceptor, M (2) ,M (4) are second and fourth order coupling matrix elements respectively. Furthermore, the third term represents the quantum interference of the RET process and signifies the controllability of the RET due to the laser field.…”
Section: (A) (D) the Results Demonstrate That Even For Moderate Lasmentioning
confidence: 99%
“…OPTICALLY CONTROLLED RET Since the RET process is fully quantum mechanical in nature, it can be formally described within the framework of quantum electrodynamics (QED) [3], [4]. We first derived the optically controlled RET rate for QDs by using the second and fourth order time dependent perturbation theory, and by applying the Fermi's golden rule [3], Γ laser = Fig.…”
mentioning
confidence: 99%
“…Within the abstraction of reduced dimensionality, for instance, this is certainly the case 19,20 . Twodimensional RET has an R −4 near-field fall off with separation, while its one-dimensional counterpart is not sensitive to separation at all.…”
Section: Introductionmentioning
confidence: 99%
“…In recent work 5 we have developed a framework of quantum electrodynamics (QED) 6,7 to address Raman scattering influenced by a second, neighboring molecule; this is one of many situations in which such a theory of fundamental coupling is applied. [8][9][10][11][12][13][14][15][16] Our interest is not only in the modification of line intensities (beyond the familiar heterogeneous spectral broadening): we have shown that it is possible to engender additional spectra lines that are not conventionally Raman active, identifying the constraints that apply. The symmetry aspects of the latter feature are the focus of the present work.…”
Section: Introductionmentioning
confidence: 99%